CBP3D – COLD BENDING OF PIPES IN 3 DIMENSIONS: SUMMARY STUDY ON THE INNOVATION, FLEXIBILITY AND RELIABILITY OF TECHNOLOGY WITH APPLICATION IN PIPING FOR THE OIL&GAS INDUSTRY (Journal of Industrial and Mechanical Engineering, 2025)
Piping exists for various applications in the industry, and pipe factories find security in operating by applying available and widely tested technologies and methods – the more background there is in the applied methods, the better. Conventional practices include activities that require welding for the manufacture of spools that will be destined for different piping systems for various applications, including the Oil&Gas industry. This raises not only the concern about the existence of a reliable technology that optimizes the piping manufacturing process by reducing the amount of welding per spool, but also the need to evaluate whether such technology is capable of providing the reliability that the Oil&Gas industry requires to guarantee operational safety and quality. This dilemma can be resolved if questions such as: can cold 3D bending successfully replace welded joints? What are the regulatory requirements that a bent pipe must meet to guarantee operational safety and quality? Does the Oil&Gas industry have a history of application? What are the benefits of this technology? Is it possible to apply 3D cold bending on an industrial scale for standardized production? What is its cost potential? This summary study answers these and other questions in search of conclusive results on this topic.
Keywords: Innovation; Technology; Piping; 3D bending; Economic Scalability; Industry; Metalworking; CBP3D